PROBLEM OF AGE-DETERMINATION IN THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA, BY MEANS OF SCALES AND OTOLITHS - Seshappa, G (Indian Journal of Fisheries, 2011)
The study of the scales of Rastrelliger kanagurta (Cuvier) collected from differentcentres during the period 1955-67 and 1969-70 showed that at all centres specimens below21 cm in total length were without scale-rings; a small percentage of specimens in the• 21-22.9 cm group showed rings, while a large percentage among those above 23 cm totallength showed the rings in all the centres, this percentage being the smallest (63.1 %) atCalicut and largest (94.3%) at Karwar. Two rings occurred frequently in specimensabove 25 cm and up to four rings occurred in the very large specimens of Vizhinjam andMandapam, but in these large specimens reading of the rings was difficult as they frequentlybecame faint and obscured as a result of the thickening of the scales subsequentto the ring-formation. The scale-rings seem to be formed as a result of a physiologicalstrain on the fish during the process of growth and ripening of the gonads and also spawning.When clear rings were not noticed in mackerel with gonads in advanced stages,there were thin margins, which indicated the beginning of ring formation. The otolithsdid not show any annuli that could be used for age-determination